2013
DOI: 10.1111/jcmm.12186
|View full text |Cite
|
Sign up to set email alerts
|

Berberine ameliorates cartilage degeneration in interleukin‐1β‐stimulated rat chondrocytes and in a rat model of osteoarthritis via Akt signalling

Abstract: Berberine, a plant alkaloid used in Chinese medicine, has broad cell-protective functions in a variety of cell lines. Chondrocyte apoptosis contributes to the pathogenesis of cartilage degeneration in osteoarthritis (OA). However, little is known about the effect and underlying mechanism of berberine on OA chondrocytes. Here, we assessed the effects of berberine on cartilage degeneration in interleukin-1β (IL-1β)-stimulated rat chondrocytes and in a rat model of OA. The results of an MTT assay and western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 37 publications
2
75
0
Order By: Relevance
“…We think the result could be mainly ascribed to the following aspects. First, in this study, definite concentrations of BBR exhibited the anti-apoptotic and chondroprotective effects on OA chondrocytes similar to previous studies [27,28]. Second, the interaction between BBR and SNP could be mutual influence and restriction so as to achieve dynamic balance for treatment.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We think the result could be mainly ascribed to the following aspects. First, in this study, definite concentrations of BBR exhibited the anti-apoptotic and chondroprotective effects on OA chondrocytes similar to previous studies [27,28]. Second, the interaction between BBR and SNP could be mutual influence and restriction so as to achieve dynamic balance for treatment.…”
Section: Discussionsupporting
confidence: 78%
“…Recent studies have demonstrated that BBR decreases IL-1b-stimulated glycosaminoglycan release and NO production, and down-regulates matrix metalloproteinases expression in vitro and in vivo [26,27]. BBR was also shown to protect articular cartilage from degeneration via activating Akt/p70S6K/S6 signaling pathway in IL-1b-induced articular chondrocytes and in a rat OA model [28]. Nevertheless, few data is available on the therapeutic mechanism for BBR on SNP-stimulated chondrocyte apoptosis.…”
Section: Introductionmentioning
confidence: 96%
“…Our results show that Phlpp1 is a regulator of endochondral bone development, as chondrocyte proliferation and matrix synthesis are enhanced in Phlpp1-deficient mice. This likely occurs due to the ability of Phlpp1 to directly control the activity of anabolic signaling pathways, including Akt2, PKC, and p70 S6 kinase, that are known facilitators of proliferation and matrix production by chondrocytes (21,37,38). Activation of these pathways triggers subsequent events, including but not limited to, Fgf18 production and downstream activation of Fgfr and Mek/Erk signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, IL-1β has been widely used as a chondrocyte apoptosis-inducing agent. When exposed to IL-1β (10 ng/mL) for 2 h, chondrocyte apoptosis is significantly increased compared to the control group [9,29]. Previously, we showed that LF inhibited Dex-induced OA apoptosis of chondrocytes at a concentration of 200 μg/mL.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…The ginsenoside Rg1 may protect chondrocytes from IL-1β-induced apoptosis via the PI3K/AKT signaling pathway [36]. Berberine ameliorates cartilage degeneration in IL-1β-stimulated rat chondrocytes and in a rat model of OA via AKT signaling [29]. It has been reported that AKT signaling is one crucial upstream signaling pathway for CREB expression [37,38].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%